Affordable gravity prospection calibrated on improved time-to-depth conversion of old seismic profiles for exploration of geothermal resources. (July 2020) - Carrier, A.; Nawratil de Bono, C.; Lupi, M.
Highlights: A two-steps inversion of gravimetric data using a priori information is performed. The gravimetric data inversion underlines the presence of faults consistent with previous active seismic observations and the strong density heterogeneity of the Tertiary sediments. The faults in the Geneva Basin could reach low Mesoizoic units and may be very good candidates for middle to high enthalpy geothermal prospection. Abstract: The world energy strategy for a sustainable development promotes the use of renewable energies. Among them, middle-enthalpy geothermal energy may be used to supply heat to service industries and urban centres. However, the costs for the acquisition of high-resolution geophysical data are still high compared to the economical return of the energy eventually extracted. This study proposes a method applied to the Greater Geneva Basin, Western Switzerland–Eastern France, to calibrate the inversion of gravity data by using old 2D seismic reflection acquisitions and available well data. First, we extract sonic logs from wells for the main geological units composing the basin. Each linear velocity versus depth relationship is extracted for each well and is used to perform a time to depth conversion of available seismic data. The influence of the heterogeneous (and heterogeneously distributed) Quaternary deposits is then removed from time data. Next, we re-calibrate the obtained geological model by applying a facies blocking approach. This allows us to obtain an updated geological model that is then used to invert gravity data. Results indicate that density anomalies are heterogeneously distributed across the basin and point out regions where well-known fault systems occur. Such regions may be selected for further geophysical prospection for higher-resolution methods. Finally, we identify a marked negative density anomaly beneath the city of Geneva. This may be interpreted as either less-compacted geological units or a well-developed fault system running below one of the most important urban centres of Europe.